Pengaruh pemberian makanan tambahan - Endang Sunartil, Madarina Julia, M.G. A (Berita Kedokteran Masyarakat (BKM), 2006)
Background: School age is the period of fast child growth so that children need sufficient and balanced nutrition. Nutrition deficiency during school age will cause children to be weak, get tired easily and ailing. Consequently, they are often absent from school and face difficulties to concentrate in their study so that this affects their academic achievement. One way to cope with problem of nutrition deficiency is by supplying complementary food to school children such as snack with nutrition value 3000k for calorie and 5 grams for protein. Objectives: The study was aimed to identifying effect of complementary food supply to concentration of elementary school children Grade V in the working area of Ngemplak II Community Health Center, Sleman District. Methods: This was a quasi experimental research with pre-post test non equivalent control group design. It was conducted in 6 elementary schools of non underdeveloped village of Ngemplak Sub district, Sleman District with as many as 136 school children as samples. Research instruments used were structured questionnaires, microtoise and digital scale. Paired samples test was used to identify effect of complementary food supply to concentration of study, whereas multivariate linear regression test was used to identify relative contribution of independent variable to dependent variable. Results: Nutrition status of respondents was categorized as good. based on Z-Score value of body weight/ height and height/age. In the preliminary study there was significant difference (p>0 001) of average score between morning concentration and afternoon concentration, There was also very significant difference of average score of concentration between treatment and control group in the morning and in the afternoon